2018
DOI: 10.7717/peerj.4277
|View full text |Cite
|
Sign up to set email alerts
|

Ants of the Monomorium monomorium species-group (Hymenoptera: Formicidae) in the Arabian Peninsula with description of a new species from southwestern Saudi Arabia

Abstract: We revise the taxonomy of the myrmicine ants of the Monomorium monomorium species-group for the Arabian Peninsula. Six species are recognized: Monomorium aeyade Collingwood & Agosti, 1996, M. clavicorne André, 1881, M. exiguum Forel, 1894, M. holothir Bolton, 1987, M. mohammedi sp. n., and M. sarawatense Sharaf & Aldawood, 2013. On the basis of the worker caste, we describe Monomorium mohammedi sp. n. from the southwestern region of the Kingdom of Saudi Arabia (KSA). We designate a neotype for Monomorium aeyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…Based on Sharaf, Al Dhafer & Aldawood (2014) and the available recent data, M. pulcher is endemic to this mountain range. This hypothesis is supported by the documented remarkable regional degree of endemism of other ant species (Collingwood, 1985; Sharaf & Aldawood, 2012; Sharaf, Aldawood & Elhawagryi, 2012; Sharaf, Aldawood & Taylor, 2012; Sharaf & Aldawood, 2013; Sharaf, Al Dhafer & Aldawood, 2018; Sharaf, Akbar & Aldawood, 2018; Sharaf et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Based on Sharaf, Al Dhafer & Aldawood (2014) and the available recent data, M. pulcher is endemic to this mountain range. This hypothesis is supported by the documented remarkable regional degree of endemism of other ant species (Collingwood, 1985; Sharaf & Aldawood, 2012; Sharaf, Aldawood & Elhawagryi, 2012; Sharaf, Aldawood & Taylor, 2012; Sharaf & Aldawood, 2013; Sharaf, Al Dhafer & Aldawood, 2018; Sharaf, Akbar & Aldawood, 2018; Sharaf et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…The M. monomorium species-group can be readily recognized by the following combination of characters in the worker caste ( Sharaf et al, 2018a ): monomorphic, with size variation; head longer than broad; mandibles smooth and masticatory margin armed with four teeth; antennae with 10–12 segments, terminating in a three-segmented club; median clypeal portion raised anteriorly and longitudinally bicarinate; eyes present with variable size, located in front of the midlength of the sides in full-face view, and with four or more ommatidia in the longest row; head smooth and shining; metanotal groove well-defined, with distinct cross-ribs; propodeal spiracle circular to subcircular; propodeal dorsum meeting declivity in a rounded angle; promesonotum and propodeal dorsum smooth; body pilosity variable but usually distinct; petiole, postpetiole and gastral tergites usually smooth.…”
Section: Resultsmentioning
confidence: 99%
“…All measurements are in millimeters and follow the standard measurements of Bolton (1987) and Sharaf et al (2018a) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bolton (2018) this genus is native to Afrotropical, Australasia, Indomalaya, Malagasy, Nearctic, Neotropical, Oceania and Palearctic bioregions. Forty three species belonging to genus Monomorium have been reported from Australia (Heterick, 2001;Heterick, 2003), forty species described from Saudi Arabia (Collingwood and Agosti, 1996;Sharaf et al, 2018), four species from Sri Lanka (Antweb, 2019), eight species from Afghanistan (Pisarski, 1970), nineteen species from Iran (Paknia et al, 2010) and twenty species have been reported from India (Bharti et al, 2016;Bolton, 2018). However in Pakistan, ants have been poorly studied.…”
Section: Introductionmentioning
confidence: 99%